Krill Oil Improves Mild Knee Joint Pain: A Randomized Control Trial. - Yoshio Suzuki; Minoru Fukushima; Keishoku Sakuraba; Keisuke Sawaki; Kazuaki Sekigawa (PLoS ONE)
Background Krill oil is an edible oil extracted from krill, a small red-colored crustacean found in the Antarctic Ocean. The administration of krill oil is reported to mitigate inflammation in patients with cardiac disease, rheumatoid arthritis, or osteoarthritis. However, the effect of krill oil on mild knee pain has not yet been determined. Objective To assess the effect of krill oil on mild knee pain. Design A randomized, double-blind, parallel-group, placebo-controlled trial of fifty adults (38-85 years old) with mild knee pain attending the Fukushima Orthopedic Clinic (Tochigi, Japan) between September 2014 and March 2015. Interventions Participants were randomized to receive 2 g per day of either krill oil or an identical placebo for 30 days. Outcomes The primary outcome was improvement in subjective symptoms of knee pain as assessed by the Japanese Knee Osteoarthritis Measure (JKOM) and Japanese Orthopaedic Association score (JOA). Secondary outcomes included blood and urine biochemical parameters. Results Both the placebo and krill oil groups showed significant improvements in the questions in the JKOM and JOA questionnaires after administration. After the intervention, krill oil group showed more improvements than placebo group in two questions regarding the pain and stiffness in knees in JKOM. Controlling for age, sex, weight, and smoking and drinking habits, krill oil significantly mitigated knee pain in sleeping (P < 0.001), standing (P < 0.001) and the range of motion of both right and left knees (both P = 0.011) compared to placebo. Krill oil administration raised plasma EPA (P = 0.048) and EPA/AA ratio (P = 0.003). Conclusion This study indicates that krill oil administration (2 g/day, 30 days) improved the subjective symptoms of knee pain in adults with mild knee pain. Trial registration UMIN-CTR; ID UMIN000014413.